THE CONCENTRATION OF CHEMICAL TRACES IN GLACIER-ICE. (PART 1). FURTHER INVESTIGATIONS ON TROPOSPHERIC WASH-OUT (Part 2) - Georgii, Hans-Walter; Weber, Erich (1962)
The report deals with the results of chemical analyses of melted ice-samples from an Austrian glacier and from an Arctic island. The concentration of the different components in the ice-samples from Austria is very low compared with the concentration of the same ions in freshly fallen precipitation. This discrepancy can most certainly be explained by the mechanism of the formation of glacier-grains. The series of ice-samples collected at the Arctic island covering the period 1920 to 1960 does not show any increase of the SO4 concentration with time. The own results are finally 4 compared with data gained by other authors.